CHERISHING THE PEOPLE AND ENRICHING THE DYNASTY: OFFICIALS AND NON-ELITE PETITIONERS IN LATE MING JIANGNAN. (September 2013) - Lufrano, Richard
Abstract : In late Ming Jiangnan people below the elite but above the marginal sometimes petitioned local and provincial officials when involved in serious disputes. Lacking substantial resources and power of their own, they had a stake in an economy guided by some fundamental rules and free from the domination of the powerful and unscrupulous. Because the dynasty's fiscal foundation and the empire's stability depended in part on this large segment of the Jiangnan population, the officials sometimes issued rulings to support and protect the petitioners and had the rulings carved onto stelae strategically located in local communities. Although their interests did not always coincide, the petitioners and officials came together over certain issues vital to both. In the cases studied here, the people provided officials hampered by the limited size of formal government with crucial information and the dynasty with crucial ideological support at a time of great need; the stelae dotting local landscapes may have enhanced government's relevance and centrality.